Hybrid Testing and Variety Identification of Coconut (Cocos nucifera L.) in Sri Lanka Using Microsatellite Markers - Lalith Perera (International Coconut Community Journal, 2010)
Currently, there is no reliable method for confirmation of the identity of coconut cultivars and the legitimacy of coconut hybrids. This makes serious problems in coconut breeding and seed production as the identity of coconut cultivars/hybrids can only be approximated at the very late stages of the growth based on reproductive traits owing to long juvenile period and the perennial nature of coconut. A microsatellite (SSR) marker based approach was used to develop an identification method for coconut varieties; Sri Lanka Tall, Sri Lanka Green Dwarf and Sri Lanka Yellow Dwarf, the key parents in the breeding programmes and tall x dwarf hybrids among them, using 18 coconut specific SSR primers. The validity of using yellow colour petiole as a phenotypic marker for the identification of dwarf yellow was also investigated. Two SSR primers, namely CAC20 and CNZ6 have exhibited the potential for distinguishing coconut varieties used as parents in the breeding programme and for confirming hybridity. It was revealed that yellow colour petiole is not a reliable marker for identification of dwarf yellow variety.